Low Complexity Bit-Parallel Multiplier for a Class of Finite Fields - Huapeng Wu (2006 International Conference on Communications, Circuits, and Systems proceedings : Guilin University of Electronic Technology (GUET), Guilin Bravo Hotel, Guilin, China, June 25-28, 2006, 2006)
This short paper summarizes our recent results on construction of low-complexity bit-parallel finite field multiplier using polynomial basis. The complexity and time delay of the proposed multipliers are lower than those of the similar proposals.